Optimizing the Role of Mathematics Teachers in Developing HOTS (Higher Order Thinking Skills) Based Questions Through Research-Based Learning Outcome Analysis - Puspitasari, Nitta; Kurniati, Dian; Maulana, Dikri; Hidayah, Fauzia Nurul (Fakultas Kewirausahaan Universitas Garut, 2024)
This community service activity aims to optimize the role of mathematics teachers in developing Higher Order Thinking Skills (HOTS)-based questions through research-based learning outcome analysis. The background of this activity lies in the limited ability of teachers to design assessment instruments that demand higher-order thinking, resulting in learning processes that tend to focus on memorization and basic comprehension. The method applied in this program was a descriptive approach, implemented through training, mentoring, and question analysis workshops involving mathematics teachers at the secondary school level. The program emphasized the understanding of HOTS concepts, the development of questions based on the revised Bloom’s taxonomy, and the analysis of student learning outcomes to assess the effectiveness of the developed instruments. The results showed that teachers were able to improve their skills in designing HOTS-based questions while gaining a more objective picture of student achievement. Therefore, this program is expected to strengthen teachers’ capacity in supporting more meaningful, challenging, and relevant learning aligned with curriculum demands and 21st-century competence needs.